2020
DOI: 10.1002/pon.5389
|View full text |Cite
|
Sign up to set email alerts
|

Depression and associated factors among parents of children diagnosed with cancer at Tikur Anbessa Specialized Hospital, Addis Ababa, Ethiopia

Abstract: BackgroundThe global cancer burden is estimated to have risen to 18.1 million new cases and 9.6 million deaths in 2018. The period of child's diagnosis negatively influences parents socially and psychologically leading to depression.ObjectivesThe aim of the study was to assess the prevalence of depression, its associated factors and parent's experience towards care of their cancer diagnosed child.MethodsA mixed approach quantitative and qualitative cross‐sectional study was employed between 15 March and 1 Apri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…Among the psychological symptoms of more than half of the parents, depression and trait anxiety levels were moderate, and social support was above the average score. In the current literature, the depression levels of the parents of children diagnosed with cancer were similar to our study (Boztepe et al, 2019;Mekonnen et al, 2020). In the study of Peterson et al (2020), they examined the change in emotional symptoms in the 6-month period in caregivers of children with newly diagnosed leukaemia and solid tumours; it is observed that the parents of children with leukaemia and solid tumours have borderline anxiety levels at the time of diagnosis, while parents of children with solid tumours continue to have borderline anxiety levels at the time of diagnosis and 6 months later (Peterson et al, 2020).…”
Section: Discussionsupporting
confidence: 88%
“…Among the psychological symptoms of more than half of the parents, depression and trait anxiety levels were moderate, and social support was above the average score. In the current literature, the depression levels of the parents of children diagnosed with cancer were similar to our study (Boztepe et al, 2019;Mekonnen et al, 2020). In the study of Peterson et al (2020), they examined the change in emotional symptoms in the 6-month period in caregivers of children with newly diagnosed leukaemia and solid tumours; it is observed that the parents of children with leukaemia and solid tumours have borderline anxiety levels at the time of diagnosis, while parents of children with solid tumours continue to have borderline anxiety levels at the time of diagnosis and 6 months later (Peterson et al, 2020).…”
Section: Discussionsupporting
confidence: 88%
“…These stages are consistent with the stages of grief described by Elisabeth Kübler-Ross and discussed in her book titled On Death and Dying [ 32 ]. Prolonged negative emotional responses influence the development of an increased sense of hopelessness [ 25 , 33 , 34 ], and the occurrence of anxiety disorders, depressive disorders, and even PTSD [ 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The factors which contribute to women’s resignation from their professional career include the need to perform the role of mother, a patriarchal social system and the earnings, which are frequently lower than in the case of men. At the same time, mothers who become an important part of a therapeutic team are more vulnerable to emotional and physical overload as compared to fathers [ 5 ]. Although Pinquart [ 33 ] and Baters [ 28 ] indicated a higher level of perceived stress in women as compared to men, Rahmani et al [ 4 ] did not find any significant differences in the incidence of negative emotions depending on parents’ gender.…”
Section: Discussionmentioning
confidence: 99%
“…Although Pinquart [ 33 ] and Baters [ 28 ] indicated a higher level of perceived stress in women as compared to men, Rahmani et al [ 4 ] did not find any significant differences in the incidence of negative emotions depending on parents’ gender. On the other hand, the meta-analysis of van Warmerdam [ 34 ] and the study conducted by Mekonnen [ 5 ] may lead to a conclusion that there are also other factors which may be responsible for the onset of depression such as single parenthood or lack of support [ 5 ]. The current study did not assess these variables.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation